Konflik Norma UU BPJS 2011 dengan UU SJSN 2004 dalam Sistem Jaminan Sosial: Norm Conflict Between BPJS Law 2011 and SJSN Law 2024 in Social Security System - Ariyanti, Annisa Tri; Aisyah, Safirah (Magister Ilmu Hukum - Universitas Hang Tuah, 2025)
The normative conflict between Law No. 24 of 2011 on BPJS and Law No. 40 of 2004 on SJSN has led to regulatory disharmony in the implementation of Indonesia’s National Health Insurance (JKN). The primary discrepancy lies in the legal subjects authorized to establish cooperation agreements between BPJS and healthcare providers, resulting in legal uncertainty and affecting both access to healthcare services and the efficiency of INA-CBGs-based payment mechanisms. This study aims to examine the legal dimensions of this conflict and to propose regulatory harmonization strategies to ensure justice and sustainability within the JKN system. A normative legal research method is employed, using a statutory and conceptoal approach with qualitative-descriptive analysis of secondary legal materials. The findings reveal that the norm conflict has systemic implications for contractual administration, hospital financial sustainability, and potential moral hazard ultimately harms both JKN participants and healthcare providers. The inaccuracy of the INA-CBGs-based payment system, which does not reflect the actual cost of medical services, further exacerbates the situation, leading to the emergence of various fraudulent practices such as upcoding, repeat claims, and administrative manipulation.Legislative reform, INA-CBGs tariff evaluation, and the establishment of a tripartite negotiation forum are recommended to reinforce legal certainty and social equity in the delivery of national health services.